2018
DOI: 10.1111/fare.12328
|View full text |Cite
|
Sign up to set email alerts
|

Hold on Tight: Coping Strategies of Persons With Bipolar Disorder and Their Partners

Abstract: Objective To explore coping strategies for persons with bipolar affective disorder and their partners. Background Bipolar disorder poses interpersonal and practical challenges for patients and their partners. Although the divorce rate is high among persons with bipolar disorder, few studies have examined how these people and their partners cope with the condition. Method 11 persons with bipolar affective disorder and 10 partners of people with bipolar affective disorder were interviewed separately about coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Iseselo et al ( 2016 ) cited that caregivers learn to accept and reconcile with the disability or unexpected behaviour of the relative who is mentally ill in order to avoid the frustration and disappointment that could result from the patient’s deviant behaviour. Similarly, Granek et al ( 2018 ) found that partners of bipolar patients particularly discussed that it was helpful to dodge strong emotional reactions, use acceptance and take it one day at a time during the more trying times. Other participants talked of not spending much of their time thinking about the effects of Bipolar Disorder excessively, and instead trying to focus on positive aspects.…”
Section: Discussionmentioning
confidence: 97%
“…Iseselo et al ( 2016 ) cited that caregivers learn to accept and reconcile with the disability or unexpected behaviour of the relative who is mentally ill in order to avoid the frustration and disappointment that could result from the patient’s deviant behaviour. Similarly, Granek et al ( 2018 ) found that partners of bipolar patients particularly discussed that it was helpful to dodge strong emotional reactions, use acceptance and take it one day at a time during the more trying times. Other participants talked of not spending much of their time thinking about the effects of Bipolar Disorder excessively, and instead trying to focus on positive aspects.…”
Section: Discussionmentioning
confidence: 97%
“…However, they most often actively approach aversive stimuli. It is advisable to pay attention to this aspect of functioning in clinical practice because some strategies, i.e., denial, discharge, use of psychoactive substances, blaming, seeking instrumental support (which, according to research, are more frequent in patients than in the healthy population), affect the maintenance of psychopathology ( Granek et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A religious frame of reference may give a name to and understanding of human suffering and can provide access to religious or spiritual resources. It was an important way to manage the illness, both for patients and their relatives, in a qualitative Israeli study of coping strategies of patients and partners (Granek et al 2018). According to a Turkish study (Çuhadar et al 2015), religious coping most frequently occurred among outpatients with an adaptive coping attitude focused on healthy behavior, irrespective of psychotic or manic symptoms.…”
Section: Religious Coping and Intrinsic Religiositymentioning
confidence: 99%